Acute effect of exercise with or without the integration of cooperative activities on inhibitory control in preadolescent school children - Melanie Berger; Markus Gerber; Sebastian Ludyga (Current Issues in Sport Science, 2025)
Introduction Inhibitory control describes the ability to resist distractions and to suppress dominant responses to achieve a specific goal (Miyake & Friedman, 2012). Higher inhibitory control is associated with an increased on-task behaviour in the classroom (Ludyga et al., 2022). Meta-analytical findings suggest that single exercise sessions can elicit transient enhancements in this aspect of executive function (Oberste et al., 2019). Experiencing supportive social interactions and cooperation also appear to positively influence inhibitory control (Koomen et al., 2020; Pilcher & Bryant, 2016). As exercise can be adapted to demand and stimulate cooperation, it has much potential to positively influence inhibitory control. We examined the effect of acute exercise with or without the integration of cooperative activities on inhibitory control in preadolescent school children.